Removal of some organic dyes by acid-treated spent bleaching earth - Lee, Chnoong Kheng; Low, Kun She; Gan, P. Y. (Taylor & Francis, 1999)
Acid treated spent bleaching earth was prepared by treating spent bleaching earth, a waste material from the palm oil industry, with 20% sulphuric acid and heated at 350°C for three hours. This material can efficiently sorb a variety of organic dyes especially reactive and acid dyes, with maximum sorption capacity in the order of 2–300 mg g−1. The applicability of both the Langmuir and Freundlich isotherms to the experimental data indicates that both physicosorption and chemisorption were involved in the sorption process.